EFFECTS OF NANO CHITOSAN MOUTH SPRAY ON THE EPITHELIAL THICKNESS IN THE TRAUMATIC ULCUS HEALING PROCESS (In vivo) - Recita Indraswary; Rizki Amalina; Arif Firmansyah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Traumatic ulcer is one of the most common oral mucosal lesions, which are caused by physical trauma. The prevalence of traumatic ulcers in this world is 83.6%. Ulcers cause pain, difficulty in articulation, mastication and swallowing causing discomfort to the patient. The aim of this study is to analyze the effect of nano chitosan mouth spray on epithelial thickness in the healing process of traumatic ulcers.Methods: This research was true experimental type using post test only control group design with the number of samples are 27 rats divided into three groups. The treatment group was given nano chitosan mouth spray, the positive control group was given aloclair plus spray and the negative control group was given aquadest. After 7 days of treatment, the ulcer tissue was observed using a light microscope, then the average thickness of the epithelium was calculated. They were then analyzed using one-way ANOVA and LSD tests.Results: The results showed difference in the average value of each group. The treatment group is higher than the positive control group and the negative control group with an average epithelial thickness (19.42 ± 2.11). Meanwhile, the negative control group is the lowest group among the three groups with an average epithelial thickness (5.72 ± 0.77). The results based on the One Way Anova parametric test, the value of p = 0.000 (p <0.05)Conclusion: The conclusion obtained is that there is an effect of chitosan nanomouth spray on epithelial thickness on the healing process of traumatic ulcers in male Wistar rats after 7 days of treatment